CURRENT STATE AND DIRECTIONS OF DEVELOPMENT OF BANK LENDING TO SMALL AND MEDIUM BUSINESS IN UKRAINE (International Journal of Innovative Technologies in Economy, 2022)
The article analyzes the current trends in bank lending to small and medium-sized businesses in Ukraine and banking products and programs to help small and medium-sized businesses provided by individual state-owned banks. Conclusions on the current situation are substantiated and the directions of development of bank lending to small and medium business are determined.